2005
DOI: 10.1123/mcj.9.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Information Processing and Constraints-based Views of Skill Acquisition: Divergent or Complementary?

Abstract: Since the middle of the nineteenth century, movement scientists have been challenged to explain processes underlying the control, coordination, and acquisition of skill. Information processing and constraints-based approaches represent two distinct, often perceived as opposing, views of skill acquisition. The purpose of this article is to compare information processing and constraints-based approaches through the lens of Fittsʼ three-stage model and Newellʼs constraints-based model, respectively. In essence, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 77 publications
(76 reference statements)
2
32
0
Order By: Relevance
“…Gaining this intertwined relationship between sub-systems of action, cognition and perception, which support interactions with a performance environment, is the fundamental basis for using technologies like VR systems to enrich athlete learning and performance. Interactions with key informational variables in a performance context act as boundaries that shape emergent patterns of behaviour (Anson, Elliott, & Davids, 2005).…”
Section: How Vr Systems Can Support Interactions Of Athletes With Tasmentioning
confidence: 99%
“…Gaining this intertwined relationship between sub-systems of action, cognition and perception, which support interactions with a performance environment, is the fundamental basis for using technologies like VR systems to enrich athlete learning and performance. Interactions with key informational variables in a performance context act as boundaries that shape emergent patterns of behaviour (Anson, Elliott, & Davids, 2005).…”
Section: How Vr Systems Can Support Interactions Of Athletes With Tasmentioning
confidence: 99%
“…As we shall see, the respective contributions depend both on skill level or stage of learning and on the nature and constraints of the task (see Anson, Elliot, & Davids, 2005;Bernstein, 1996). Assuming that controlled processing, but not automatic processing, relies heavily on the availability of a limited-capacity attentional resource (i.e., working memory), it follows that skilled performance depends on either efficient allocation of conscious attentional resources or automatization of certain subcomponents of the skill to free conscious resources.…”
Section: Controlled and Automatic Processingmentioning
confidence: 99%
“…Recently, Anson, Elliott, and Davids (2005) compared these two approaches and concluded that the models of motor-skill acquisition developed from each are more similar than they are different. Among other points made by Anson et al is that the development of what they call the constraints-based approach was based to a large extent on a misunderstanding about human information processing.…”
Section: Promise Of Information Processing 273mentioning
confidence: 97%